2022
DOI: 10.1037/pspi0000380
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination is not just Black and White in romantic relationships: A consideration of perspective taking and self-expansion.

Abstract: Interracial relationships can satisfy our human need for interpersonal bonds, but face adversity due to racial discrimination. This adversity is not parallel for the involved partners, however, in ways that have implications for relationship outcomes. As such, in the current research, we considered that discrimination may provide an avenue for positive self-expansion for a White partner, insofar as they use it to learn more about their partner's worldview and experience. This is important, as facing racial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Cultural sharing can include a variety of behaviors such as partners engaging in experiences involving their cultures (e.g., participating in a partner’s cultural practices) or having supportive discussions about their experiences as members of different cultures. Recent work has found that when partners in interracial relationships share their experiences of discrimination and engage in perspective-taking, they report more self-expansion (i.e., personal growth), and subsequently greater relationship quality (Caselli & Machia, 2022). Cultural sharing is also linked with greater self-expansion and in turn both partners’ relationship quality (West et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural sharing can include a variety of behaviors such as partners engaging in experiences involving their cultures (e.g., participating in a partner’s cultural practices) or having supportive discussions about their experiences as members of different cultures. Recent work has found that when partners in interracial relationships share their experiences of discrimination and engage in perspective-taking, they report more self-expansion (i.e., personal growth), and subsequently greater relationship quality (Caselli & Machia, 2022). Cultural sharing is also linked with greater self-expansion and in turn both partners’ relationship quality (West et al, 2022).…”
Section: Introductionmentioning
confidence: 99%